Predictors of acute heart failure in patients during the acute period of Q-wave myocardial infarction - Syvolap, V. D.; Kapshytar, N. I. (Zaporozhye Medical Journal, 2019)
The aim was to identify predictors of acute heart failure (AHF) in patients with acute Q-wave myocardial infarction (MI). Materials and methods. A total of 139 patients in the acute period of Q-wave MI were examined, average age was 66.00 ± 0.97 years (M ± m). Patients were divided into 2 groups depending on AHF presence: without AHF – 46 persons, the mean age was 61.00 ± 1.87 years (M ± m) and with developed AHF – 93 persons (Killip II, n = 51; Killip III, n = 42), the mean age was 69.2 ± 8.3 years (M ± m). The patients underwent general clinical examination, blood glucose level was determined on admission, transthoracic Doppler echocardiography was performed and copeptin and NTproBNP levels were measured. Results. According to univariate logistic regression analysis, hyperglycemia in the acute period of Q-wave MI was associated with a probable increase in the odds ratio of AHF by 1.24 times (95 % CI 1.08–1.44; P = 0.003). According to the results of the ROC-analysis, the critical level of glycemia was >9.3 mmol/l (sensitivity 47.8 %, specificity 78.3 %), the area under the ROC-curve was 0.666 (95 % CI 0.580–0.745; P = 0.0004). With the development of systolic dysfunction in the acute period of MI, the odds ratio of AHF increased by 5.69 times (95 % CI 2.47–13.14; P < 0.0001). An increase in copeptin level of more than 0.53 ng/ml (sensitivity 93.1 %, specificity 28.6 %) and the area under the ROC curve of 0.633 (95 % CI 0.543–0.716; P = 0.0086) were associated with an increase in the odds ratio of AHF by 1.39 times (95 % CI 1.06–1.83; P = 0.02). There was no dependence of AHF on NTproBNP level – OR = 1.001 (95 % CI 0.99–1.01; P = 0.36). According to multivariate logistic regression analysis, independent risk factors for AHF were the hyperglycemia level on admission of more than 9.3 mmol/l OR = 1.19 (95 % CI 1.01–1.39; P = 0.036) and left ventricular (LV) systolic dysfunction – OR = 5.24 (95 % CI 2.03–13.55; P = 0.001). Conclusions. In patients with acute Q-wave MI complicated by AHF, the admission levels of copeptin and glycemia were significantly higher andLV ejection fraction was significantly lower. The dependent risk factors for AHF in patients with acute Q-wave MI were glycemia level of more than 9.3 mmol/l, an increase in copeptin level of more than 0.53 ng/ml, andLV systolic dysfunction. Independent risk factors for AHF in the acute period Q-wave MI were hyperglycemia andLV systolic dysfunction.